2018
DOI: 10.1108/gs-01-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Audit report forecast: an application of nonlinear grey Bernoulli model

Abstract: Purpose-The widespread application of traditional grey model (GM) in different academic fields such as electrical engineering, education, mechanical engineering and agriculture provided the authors with an incentive to conduct the present empirical research in an accounting field, in particular, auditing practice. In this regard, the purpose of this paper is to employ the nonlinear type of the original GM to forecast the drastically changed data on audit reports, primarily due to the fact that the linear natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Auditing practice is considered as one of the fundamental parts of corporate liability regime. In this regard, the fulfillment of corporate liability function is primarily dependent on authentic and reliable information examined by an external and independent auditor (Salehi and Dehnavi, 2018). Audit regulations and guidance require the existence of audit opinion in an audit report.…”
Section: Audit Quality and Value Relevance Of Accounting Informationmentioning
confidence: 99%
“…Auditing practice is considered as one of the fundamental parts of corporate liability regime. In this regard, the fulfillment of corporate liability function is primarily dependent on authentic and reliable information examined by an external and independent auditor (Salehi and Dehnavi, 2018). Audit regulations and guidance require the existence of audit opinion in an audit report.…”
Section: Audit Quality and Value Relevance Of Accounting Informationmentioning
confidence: 99%
“…Heng-Shu [15] took the financial indicators of listed companies as variables and introduced Takagi-Sugeno fuzzy neural network to construct the prediction model of audit opinions. Salehi and Dehnavi [16] applied the grey model to predict audit reports and found that the Nash nonlinear grey Bernoulli model had the best prediction effect. Yao and pan et al [17] adopted stepping-regression and principal component analysis (PCA) to reduce the dimension of company characteristics and used six machine learning methods to identify fraudulent activities in financial statements of Chinese listed companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, data enhancement and discretization measures can efectively improve the prediction performance of the model. To promote the development of grey system theory, this paper develops a new grey prediction model with a time-delay polynomial based [6] NGM (1, 1, k, c) A linear function is used instead of the constant as the grey action in the traditional grey model Qian et al [7] GM (1, 1, t α ) A grey prediction model with a power term with hyperparameter α as grey action Wei et al [8] GMP (1, 1, N) A model is developed by using polynomial as the grey action of the grey model Liu et al [9] PTGM (1, 1, α) Combination of GMP (1, 1, N) and GM (1, 1, t α ) Saxena [10] OFOPGM A new data-driven grey prediction model using the time item with two hyperparameters as the action Wu et al [11] NGBM (1, 1, k, c) A NGM (1, 1, k, c) model with nonlinear Bernoulli operators Liu et al [12] NGBM (1, 1, N) A GMP (1, 1, N) model with nonlinear Bernoulli operators Ma and Liu [13] TDPGM (1, 1) A grey model with the function called time-delayed polynomial as the grey action Ma et al [14] FTDGM A model is developed by using fractional time delayed term as the grey action of the grey model Xiang et al [15] HTGM (1, 1) A prediction algorithm using hyperbolic time delayed polynomial as grey action Salehi and Dehnavi [16] NGBM ( [20] Hybrid model A combination of GM (1, 1) and VAR (1) Zhou et al [21] Hybrid model A combination of GM (1, 1) and ARIMA Saxena [2] IOGM Grey forecasting models based on internal optimization Optimization based on data enhancement methods Wu et al [22] FGM (1, 1)…”
Section: Introductionmentioning
confidence: 99%